Breaking Barriers: Sign Language and Visual Aids in a Regular English Classroom for Hearing-Impaired Students - Riza Mae Capitle; Genaro Ferrariz; Angelyn Garcitos; Ronjell Amacna; Juliet Caballero; Sophia Marie Diel (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2025)
This study explored the effectiveness of integrating sign language and visual aids into English language instruction for hearing-impaired (HI) students in inclusive classrooms. Focusing on the reading comprehension skill of identifying claims in written texts, the research assessed how multimodal strategies could enhance English language learning outcomes for both HI and hearing students. A quasi-experimental design was used, featuring pre- and post-tests based on a 25-item multiple-choice assessment aligned with Bloom’s Taxonomy. The results showed significant post-test gains for both groups, suggesting that the integration of sign language and visual aids can improve students’ ability to identify claims in English texts. Classroom observations highlighted increased collaboration and the use of varied communication strategies. The findings underscore the need for inclusive pedagogical approaches and trained educators to support equitable English language learning. Further research is recommended to validate these findings across larger, more diverse samples. This study contributes to English language teaching (ELT) by demonstrating how inclusive methods can support reading comprehension and promote language learning for all students.